Short-Term Impact of a Zero Concentrate Supplementation on Organic Dairy Production - Hoop, Daniel; Schory, Fredy (Economia agro-alimentare/Food Economy - Open Access, 2022)
This study investigates the short-term economic impact of a zero-concentrate supplementation in organic dairy production systems with Holstein cows. Based on experimental data and using prices recorded in 2018 in Switzerland, the study calculates the difference in profits between two annual herbage-based feed rations: one supplemented with 750 kg and the other containing 0 kg concentrates per cow and lactation. The cut in concentrates led to a considerable increase in the average culling rate (14.4 percentage points). If it is assumed that the culling rate cannot be lowered by means of breeding or management adjustments, a zero-concentrate supplementation leads to a 375 CHF drop in profit per cow and year, which is equivalent to a 14% decrease in the remuneration of labor input. If the culling rate could be decreased to the status quo, then not feeding concentrates leads to a smaller, non-significant decrease in profits of 141 CHF per cow and year. Overall, it is concluded that there is a short-term trade-off between profitability and a reduction in concentrates. A zero-concentrate supplementation would be economically feasible only if the culling rate can be kept under control, for instance, by using adapted cow breeds. However, high-quality roughage is a prerequisite and may be more difficult to produce in alpine regions with less favorable production conditions.